2020
DOI: 10.4097/kja.19409
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of newly developed postoperative low back pain with median versus paramedian approach for spinal anesthesia

Abstract: Background:The effects of the anesthetic technique on postdural puncture backache (PDPB) have not been specifically evaluated. The purpose of this study was to compare the incidence and severity of PDPB between median and paramedian techniques. Methods:Patients were randomized to receive spinal anesthesia by either a median (M group, n = 50) or paramedian (P group, n = 50) approach. We recorded patients' personal number of puncture attempts, surgical position, and operation duration. We investigated the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 21 publications
0
17
1
Order By: Relevance
“…This result was consistent with the study done in Germany (40%) [ 21 ]. However, the current finding is higher than the reports in the Republic of Korea (32%) [ 38 ]. This might be due to the fact that patients who had multiple lumbar puncture attempts (>3 times) were included in our study.…”
Section: Discussioncontrasting
confidence: 95%
“…This result was consistent with the study done in Germany (40%) [ 21 ]. However, the current finding is higher than the reports in the Republic of Korea (32%) [ 38 ]. This might be due to the fact that patients who had multiple lumbar puncture attempts (>3 times) were included in our study.…”
Section: Discussioncontrasting
confidence: 95%
“…The potential mechanism that initiates back pain following neuraxial anesthesia includes stretching or traumatic injury of ligaments, fascia, or bone with localized bleeding or injury to the adjacent nerve root. Musculoskeletal mechanisms are relaxation of the paraspinal muscles under anesthesia, flattening of the normal lumbar lordosis, immobility of the spine, and stretching of the joint capsules and paraspinal ligaments [ 1 , 2 , 6 , 7 ]. Especially, the lithotomy position can cause pelvic rotation, which aggravates the reduction in normal lumbar lordosis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the paramedian technique can avoid such injury of midline ligaments by inserting the needle slightly away from the midline. Previous study also showed that spinal anesthesia with the paramedian technique could reduce the incidence of back pain compared to the midline technique [ 2 , 8 , 9 ]. A recent randomized study demonstrated that the incidence of back pain was 2% and 10% in the paramedian group and the midline group, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrathecally administration of spinal anesthesia is a common anesthetic technique used in lower extremity surgeries[ 1 ]. Neurological complications, such as hematoma, infections, and temporary or permanent spinal cord injuries, can occur after spinal anesthesia[ 2 ].…”
Section: Introductionmentioning
confidence: 99%